Association between Gonial Angle and Mandibular Residual Ridge Resorption in Implant-Overdenture Patients - S Palaniappan, PL Ranganayakidevi; Yunus, Norsiah; Ibrahim, Norliza; Ahmad, Siti Fauzza; Krishnan, Anitha (UI Scholars Hub, 2025)
Objectives: The gonial angle could be one of the contributing factors for the continuous bone resorption in edentulous persons. This study aimed to examine the association between the gonial angle and RRR in edentulous patients receiving mandibular implant-supported overdenture (ISOD) and to compare different gonial angle measuring techniques. Methods: Twenty-three individuals with opposing mandibular ISOD and maxillary full dentures were recruited. The proportional area index was used to calculate the posterior RRR. Orthopantomographs (OPGs) pre- and four years post-implant insertion were compared. Comparison of the gonial angle measurements was made on 5 patients using four measurement methods: (i) Two different vertical line tracing points on OPG (exterior border points and mid-condylar points), (ii) Measurement on a 3D model using a goniometer, (iii) Lateral cephalometric view of CBCT using Mimics software. Results: The posterior RRR showed no correlation with the gonial angle (r < 0.3, p > 0.05). Between the two OPG measurement techniques, there was no discernible difference (p = 0.185), and there is a strong association between both OPG measuring techniques and CBCT readings (R2 = 0.927, 0.829). The manual measurement on the CBCT showed a modest correlation with models produced by 3D printing (R2 = 0.098). Conclusion: The mandibular gonial angle did not correlate with posterior mandibular RRR.